The Kuils River multiple: versions of an urban river on the edge of Cape Town, South Africa - Solomon, Nikiwe (Environmental Humanities South, 2022)
This thesis explores how diverse ways of knowing and being with the Kuils River, located in Cape Town, South Africa, are shaped and in turn shape the river. The management of water (in pipes and rivers) and the development of water infrastructure are deeply rooted in societal development agendas that, over time, have been embedded in discourses of empire, economic growth, state formation, sustainability and technological efficiency. When river management is informed by different agendas, the practice of management then differs across different levels of governance, research and communities, and multiple meanings of different forms of human-water relationships emerge. This study examines how the resulting tangle of meanings impacts river management practices in Cape Town, and in turn shape the well-being of people and more-than-human communities living in and with the river. Specific research questions include: What are the diverse ways of knowing and relating to the Kuils River? How are these diverse ways of knowing and relating enacted? How does this shape river and capital flows, governance and the well-being of multispecies communities? Based on roughly three years of transdisciplinary methods of ethnographic fieldwork, archival research and water testing in the Kuils River catchment area, this thesis explores how lives, politics, technology and environment are impacted by river management practices in Cape Town and how these produce different versions of the river, which in turn shape the everyday of the Kuils and how it is managed. In focusing on the multiple interactions with the Kuils River and its associated water bodies and on the flow of the river itself at community and governance levels, this thesis foregrounds differing meanings of ‘environment' and their management and how these versions limit the achievement of urban and peri-urban wellbeing. This thesis highlights the divergent experiences of the managed Kuils River (including those of people and of the water body) to demonstrate that particular logics have geological effects that will be experienced far into the future.